INDIRECT RESTORATION OF A CENTRAL INCISOR USING A CAD/CAM-MILLED RESIN: A CLINICAL CASE REPORT - Guilherme Miguel Moreira De Oliveira; Ana Karolina Peters; Letícia Silva De Andrade; Emily Dutra Amaral Meggiolaro Guimarães Veiga; Alice Quirino Itaborahy; Sebastião Diogo Fiochi Almeida Matozo; Laura Gábrio Gomes Duarte; Amanda Andrade Pitman; Maurício Verissimo Pereira; Valdir Cabral Andrade; Fabíola Pessôa Pereira Leite (ARACÊ, 2026)
The aesthetic restoration of anterior teeth presents a challenge in restorative dentistry due to the need to harmoniously reproduce optical, morphological and functional characteristics. In this context, CAD/CAM-milled composite resin indirect restorations offer a conservative, predictable and cost-effective alternative. This paper reports the clinical case of a patient who sought treatment following the fracture and loss of a veneer on the left upper central incisor. Given the aesthetic demands of the case and the patient’s desire for a natural result, it was decided to fabricate an indirect composite resin restoration using a fully digital workflow. Planning was carried out using intraoral scanning with the Primescan 2 system and restoration design in the CEREC software. The restoration was fabricated from a block of composite resin milled on the CEREC Primemill. To mask the darkened substrate (A4) and harmonise the restoration with the adjacent whitened teeth, an opaque light-curing resin cement (Allcem Veneer WO, FGM) was used. The results demonstrated excellent aesthetic integration, faithful reproduction of the contralateral anatomy and high patient satisfaction. It is concluded that milled composite resin combined with digital planning constitutes an effective and conservative alternative for single-tooth aesthetic restorations in the anterior teeth.